Optimizing Learning Management System (LMS) Based Assessment in Aqidah Akhlak Learning Oriented toward Higher Order Thinking Skills (HOTS) - Rizqi Muyasharoh; Aji Joko Budi Pramono (The Future of Education Journal, 2026)
This study aims to analyze the optimization of Akidah Akhlak learning assessment based on Learning Management System (LMS) oriented towards Higher Order Thinking Skills (HOTS) at Al-Azhar Cairo Islamic Elementary School, Sragen. The focus of the study includes the development of HOTS assessment instruments, the implementation of LMS-based assessments, their effectiveness in developing students' critical thinking skills, as well as obstacles and strategies for optimizing their implementation. The study used a qualitative approach. Data were collected through interviews, observations, and documentation of teachers involved in Akidah Akhlak learning. Data analysis was carried out using thematic analysis through the stages of open coding, axial coding, and selective coding with the help of the R program for visualization and mapping of relationships between codes, categories, and themes. The results of the study show four main themes, namely: (1) the development of LMS-based HOTS assessment instruments carried out through analysis of learning outcomes, preparation of indicators, grids, contextual questions, and assessment rubrics; (2) the implementation of LMS that supports more systematic, efficient, and documented assessment management; (3) the effectiveness of HOTS-oriented LMS-based assessments in improving students' critical, analytical, reflective, and independent learning abilities; and (4) implementation constraints including limited internet network, technical obstacles, and challenges in developing HOTS instruments, which were addressed through teacher training, continuous instrument evaluation, and school infrastructure support. The research findings indicate that the integration of LMS and HOTS contributes positively to improving the quality of Aqidah Akhlak learning assessments and the development of students' high-level thinking skills.